Computational simulation of laminar heat convection of nanofluids in a circular tube and squared duct (2016)
Nanofluids are colloidal suspensions of nanometer-sized particles (metals, metallic oxides or carbon nanotubes) in a base fluid (polar or non-polar). Nanofluids have interesting properties that make them useful especially in the design of compact heat transfer equipment. Laminar convective heat transfer of nanofluids (water, Al2O3) in a square and circular ducts has been studied numerically using the software ANSYS/FLUENT 12.1. Results for the Nusselt number, skin coefficient friction, temperature and velocity profiles are presented for four nanoparticle volume fractions (j = 0 - 20%) and Reynolds numbers (Re = 800, 1300 and 2000). For the studied Re numbers, Nu is decreased by 12% and 10%, when j is increased from 0% to 10% and from 10% to 20%, respectively. Regard to the skin friction factor, the obtained value is increased around a 30% when j is increased 10%.